Myocardial Injury Leading to Left Ventricular Failure: A COVID-19 Complication - Rashid, Muhammad Humayoun; Piracha, Muhammad Usman; Aisha, Azka; Komel, Aqsa; Ahmad, Mehjabeen; Fatima, Meher; Saif, Usama Bin; Farooque, Umar (Cardiology and Cardiovascular Medicine, 2020)
SARS-CoV-2 has been associated with a lot of complications one of which is myocardial injury which is still a subject under study. Here we present a case of a 63 years old diabetic man with signs of left ventricular failure and clear evidence of myocardial injury, later diagnosed as COVID-19. In the setting of cardiac emergency medical professionals need to have a high index of suspicion early on during the management.